Application progress of Non-invasive Micro-test Technology in environmental bioremediation and stress physiology research - Jiang, Wenxuan; You, Shaohong; Shi, Yucui; Jiang, Pingping; Chen, Mouyixing; Yang, Xuemeng (Journal of plant interactions, 2023)
Non-invasive Micro-test Technology (NMT) measures the ions/molecules in and out of the samples in a real-time, three-dimensional and dynamic manner without damaging the biological samples to obtain ions/molecules concentration, flow rate and movement direction, providing evidence for the study of the transport mechanism of biological and external environmental substances. This paper introduces the structure, operation system and technical advantages of NMT, and compares it with other ion testing technologies. Additionally, we conclude that it possesses the following attributes: no damage to biological activity, large range of measurable samples and targets, high sensitivity, and rich data content. Furthermore, its application progress in recent years has been reviewed and prospected from the perspectives of environmental bioremediation and stress physiology, which provides a reference for sustainable biological and environmental research.